2013
DOI: 10.1128/ec.00339-12
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Quinolinic Acid, an Intermediate in the Kynurenine Pathway, for Utilization in NAD + Biosynthesis in the Yeast Saccharomyces cerevisiae

Abstract: NAD؉ is synthesized from tryptophan either via the kynurenine (de novo) pathway or via the salvage pathway by reutilizing intermediates such as nicotinic acid or nicotinamide ribose. Quinolinic acid is an intermediate in the kynurenine pathway. We have discovered that the budding yeast Saccharomyces cerevisiae secretes quinolinic acid into the medium and also utilizes extracellular quinolinic acid as a novel NAD ؉ precursor. We provide evidence that extracellular quinolinic acid enters the cell via Tna1, a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 27 publications
2
46
0
Order By: Relevance
“…To identify the source of elevated NR in ssy5⌬ cells (Fig. 2F), we examined the gene expression of pathways known to produce and salvage NAD ϩ and NR (8,10,(45)(46)(47). Expression levels of the genes in NAD ϩ synthetic pathways generally remained similar between WT and ssy5⌬ cells as we expected (Fig.…”
Section: Yeast Mutants With Reduced Sps Signaling Exhibit Increasedmentioning
confidence: 57%
“…To identify the source of elevated NR in ssy5⌬ cells (Fig. 2F), we examined the gene expression of pathways known to produce and salvage NAD ϩ and NR (8,10,(45)(46)(47). Expression levels of the genes in NAD ϩ synthetic pathways generally remained similar between WT and ssy5⌬ cells as we expected (Fig.…”
Section: Yeast Mutants With Reduced Sps Signaling Exhibit Increasedmentioning
confidence: 57%
“…Ohashi et al . showed that quinolinic acid (QA) is also produced and excreted like NR (16). Thus, it is possible that pyridine nucleotides and their metabolites are involved in a variety of cellular processes and balancing their concentrations would be critical for the regulation of these processes.…”
Section: Discussionmentioning
confidence: 99%
“…NA can be generated from Nam mediated by the Nam deamidase Pnc1 ( p yrazineamidase and n i c otinamidase) as part of the salvaging reactions. Both NA and QA can also be acquired from the environment by the NA transporter Tna1 ( t ransporter of n icotinic a cid) (16,17). De novo synthesis and NA/Nam salvaging pathways converge at NaMN, which is converted to deamido-NAD + (NaAD) by transferring the AMP moiety of ATP by Nma1 and Nma2 (NMNATs).…”
Section: Overview Of Nad+ Biosynthesismentioning
confidence: 99%
“…As part of NA/NAM salvage, another phosphoribosyltransferase, Npt1, converts NA into NaMN (Preiss et al, 1958; Preiss et al, 1958). NA is mainly salvaged from Nam by Pnc1 deamidase, but the NA transporter, Tna1, also imports both NA and QA (Llorente et al, 2000; Ohashi et al, 2013). Next, NaMN a denylyltransferases, (NaMNATs), Nma1 and Nma2, convert NaMN into nicotinic acid adenine dinucleotide (NaAD or deamido-NAD + ) by transfer of the AMP moiety from ATP.…”
Section: Nad+ Biosynthetic and Signaling Pathways In Yeastmentioning
confidence: 99%
“…In yeast, we recently showed that NMN is constantly converted into NR, which is more mobile and readily excreted, re-assimilated or sent to storage (Kato et al, 2014). The NAD + intermediate, QA, was also shown to be produced and excreted like NR (Ohashi et al, 2013). Additionally, Nam is a product and inhibitor of NAD + -dependent deacetylase, Sir2, thus Nam clearance is critical for Sir2 activity and life span (Gallo et al, 2004) (see 8.1 Sir2 and NAD + metabolism).…”
Section: Nad+ Biosynthetic and Signaling Pathways In Yeastmentioning
confidence: 99%